3D-ASC-Exos as a novel drug carrier for glioma treatment - Han, Xintong; Li, Xin; Yan, Xinrui; Zhang, Yu; Liu, Chang; Liu, Wei; Han, Rui; Li, Yaxin; Li, Jianming; Diao, Naichao; Jia, Boyin; Du, Rui (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIt is known that extracts from deer antler stem cells have an inhibitory effect on glioma growth. Therefore, it is hypothesized that exosomes derived from deer antler stem cells (ASC-Exos) can be used as a new drug carrier for the treatment of glioma.MethodsTo begin with, we established a 3D culture system to obtain more exosomes and characterized the 3D-ASC-Exos. Subsequently, we loaded TMZ into 3D-ASC-Exos. Evaluate the effects of 3D-ASC-Exos loaded with TMZ on glioma cell proliferation, migration, invasion, and apoptosis at the cellular level. Additionally, the safety and efficacy of 3D-ASC-Exos loaded with TMZ against glioma were evaluated using tumor-bearing mice.ResultsCompared with the 2D-ASC-Exos obtained from the traditional 2D culture, the 3D-ASC-Exos obtained from our constructed 3D culture system were concentrated nearly 30 times in the culture medium volume, which was more convenient for subsequent puriffcation. The two forms of ASC-Exos had similar morphologies and surface markers, but 3D-ASC-Exos were enriched with more miRNAs related to tumor suppression. In vitro experiments demonstrated that 3D-ASC-exosomes loaded with temozolomide (TMZ) inhibited the proliferation, migration and invasion abilities of glioma cells and promoted the apoptosis of glioma cells. The vivo tumor-bearing mouse model demonstrated that 3D-ASC-Exos loaded with TMZ exerted tumor-suppressive effects by inhibiting tumor growth and promoting tumor apoptosis. Meanwhile, the treatment with 3D-ASC-Exos loaded with TMZ caused no damage to the various tissues and organs of mice compared with the TMZ group.Discussion3D-ASC-Exos can be used as a novel drug carrier for glioma treatment. The development of 3D-ASC-Exos as a drug carrier not only provides a better strategy for tumor treatment, but also demonstrates the broad potential of exosomes in targeted tumor therapy.